2012
DOI: 10.1128/jvi.06534-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Ostreid Herpesvirus 1 (Malacoherpesviridae) Specimens by Sequencing Amplified Fragments from Three Virus Genome Areas

Abstract: bAlthough there are a number of ostreid herpesvirus 1 (OsHV-1) variants, it is expected that the true diversity of this virus will be known only after the analysis of significantly more data. To this end, we analyzed 72 OsHV-1 "specimens" collected mainly in France over an 18-year period, from 1993 to 2010. Additional samples were also collected in Ireland, the United States, China, Japan, and New Zealand. Three virus genome regions (open reading frame 4 [ORF4], ORF35, -36, -37, and -38, and ORF42 and -43) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
119
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 21 publications
(25 reference statements)
9
119
1
Order By: Relevance
“…4B, most closely resembles the ancestral sequence for this cluster. This finding is in contrast to previous results (Renault et al 2012) which suggested that the 2002 sample from China falls within the OsHV-1 clade containing the reference strain. The sequence of the microsatellite region of this sample also suggests that it belongs to the microvariant cluster (Fig.…”
Section: Sequence Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…4B, most closely resembles the ancestral sequence for this cluster. This finding is in contrast to previous results (Renault et al 2012) which suggested that the 2002 sample from China falls within the OsHV-1 clade containing the reference strain. The sequence of the microsatellite region of this sample also suggests that it belongs to the microvariant cluster (Fig.…”
Section: Sequence Analysiscontrasting
confidence: 99%
“…The Australian Os HV-1 clustered within the microvariant clade and was most similar to samples sequenced from outbreaks in 2010 in New Zealand, Japan and France. As noted previously (Renault et al 2012), the majority of sequences within the microvariant cluster are derived from samples collected from 2008 on wards. One possible exception to this is an Irish variant (GenBank Accession Number JQ963169) which was identified in C. gigas adults experiencing mortalities in 2003 and 2004.…”
Section: Sequence Analysismentioning
confidence: 73%
See 1 more Smart Citation
“…genotypes were associated with sporadic mortality events of Crassostrea gigas larvae and spat (oysters less than 1 year old) (Garcia et al, 2011). From 2008, Crassostrea gigas mortalities greatly increased on the French coast and spread to other European countries (Renault et al, 2012). These high mortalities were linked to the emergence of a newly described OsHV-1 genotype labelled mVar (Segarra et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently together to polyploid production, studies on genetic selection with the purpose of obtaining a more genetically resistent oysters strain/family have started [49,[50][51][52]. Moreover, studies on oyster immune response to Ostreid Herpesviruses and newly appeared pathogenic bacteria, such as Vibrio aestuarianus, [53,54] are now developing [55][56][57][58][59][60][61][62][63][64][65][66][67]. …”
Section: Virus Infectivitymentioning
confidence: 99%